Becoming a forerunner in foresight : Key elements of success in organizational foresight - Sinkkilä, Linnea (My University, 2021)
As previous foresight studies show, successful foresight activities are the key to organization’s long-term survival and increased performance. But what are the elements that constitute successful foresight? And furthermore, how organizations understand “foresight success”? This thesis approaches the issue of successful foresight in organizations by building an overview of factors that promote or hinder organizational foresight. The aim is to improve organizational foresight practices by increasing the understanding of foresight success elements. An organization that cultivates these elements can eventually transform into a forerunner in foresight. Foresight success and success factors are first examined through previous foresight studies and further considered through empirical material. The selected approach is qualitative inquiry: by interviewing 12 Finnish organizations of which six can be considered as forerunners in foresight, a deeper understanding of organizational foresight success is constructed. Empirical findings are further supported by theoretical framework of foresight maturity models, in which elements of foresight are depicted as organizational capabilities that develop over time. As a result, this study confirms the importance of factors identified in previous foresight research that promote, or conversely hinder, foresight successfulness in organizations. These factors include methodological solidness, employees’ and managers’ skills in futures thinking, foresight supporting technology, diversity and networks, mental models and mindsets of foresight participants, organizational learning and learning traps, structural integration of foresight, foresight as an organizational routine, and organizational culture. Two additional elements, focus and communication, were identified from the basis of empirical data. Of these, especially communication is highly significant to organizational foresight success. The question of what is meant by foresight success is answered from organizations’ perspective: what constitutes as foresight success is socially constructed in organizations, and its meanings and definitions vary depending on the context.

Aiemmissa tutkimuksissa onnistuneen ennakoinnin on osoitettu olevan yhteydessä organisaation selviytymiseen pidemmällä aikavälillä sekä sen lisääntyneeseen suorituskykyyn. Mutta mistä elementeistä onnistunut ennakointi koostuu? Entä miten organisaatiot itse käsittävät ennakoinnin ”onnistumisen”? Tässä tutkimuksessa onnistunutta ennakointia pyritään tarkastelemaan luomalla kokonaiskuva tekijöistä, jotka edistävät tai heikentävät ennakointia organisaatioissa. Tavoitteena on kehittää ennakointikäytäntöjä lisäämällä ymmärrystä ennakoinnin menestystekijöistä. Organisaatiot, jotka kehittävät näitä tekijöitä toiminnassaan, voivat ajan myötä muuntautua ennakoinnin edelläkävijöiksi. Onnistunutta ennakointia tarkastellaan aiempien tutkimusten ja empiirisen aineiston kautta. Lähestymistapana on kvalitatiivinen haastattelututkimus: 12 suomalaisen organisaation (joista kuutta voidaan pitää edelläkävijöinä ennakoinnissa) näkemyksistä rakentuu kuva onnistuneesta ennakoinnista organisaatioissa. Empiirisiä havaintoja tukee ennakoinnin maturiteettimalleista koostuva teoreettinen viitekehys, jossa ennakoinnin elementit kuvataan organisaation ajan myötä kehittäminä ominaisuuksina. Tutkimuksen tulokset vahvistavat aiempien tutkimusten havaintoja ennakointia tukevista tai estävistä tekijöistä. Tällaisia tekijöitä ovat vankka metodologia, työntekijöiden ja johtajien kyky tulevaisuusajatteluun, ennakointia tukeva teknologia, moniäänisyys ja verkostot, ajattelua ohjaavat mallit ja asenteet, organisaation oppimiskyky ja oppimisen sudenkuopat, ennakoinnin integraatio organisaation toimintoihin ja sen rutinoituminen sekä organisaation kulttuuri. Lisäksi haastatteluista tunnistettiin edellisten lisäksi vielä kaksi tekijää: ennakoinnin fokus ja viestintä. Näistä etenkin viestinnällä on keskeinen rooli ennakoinnin onnistumiseen organisaatioissa. Kysymystä siitä, mitä on onnistunut ennakointi, määrittää ennen kaikkea konteksti: kokemus ennakoinnin onnistumisesta rakennetaan organisaation toimijoiden välisessä vuorovaikutuksessa, ja sen määritelmä vaihtelee organisaation tavoitteista ja päämääristä riippuen.
Keywords: foresight success, organizations, maturity models